Analysis of Screwed Shaft Failure using the Process Simulation of Loaded Torsion - Vita Mustika; Agus Triono; Koekoeh K. Wibowo (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2020)
The paper present the result of the study on the use of simulation software of ANSYS R15.0 version in attempt to simulate the load which is working on a screwed shaft of a shaping machine. This shaft was broken down during normal working and within limit of its life time. Therefore, the simulation would try to find out the cause of the failure. In order to simulate the load, the mechanical properties and chemical composition of the shaft were used as the input for modeling. The shaft is made of medium carbon steel of S 45 C in round shape. The finite element method (FEM) was used for analyzing. The modeling was started with a 3D redrafting the real dimension of the shaft in a computer aided design (CAD) model, then imported to the ANSYS system into FEM format. The mechanical and physical properties of the material was entered as the engineering data. Meshing was made to divide the component into several small elements. A combination of static and torsion load was applied to the shaft with a fixed position. The simulation results shown that von mises stress of 4.546 MPa was achieved. While, the first principal stress of 4.518 MPa, the third principal stress of 0.538 MPa. Other result revealed that the displacement was 0.001602 mm. Simulation also indicate that failure occurs at the slot a place where the pin was inserted to lock between the shaft and the bevel gear. The result is in accordance with the real failure of the shaft. To conclude, the ANSYS with FEM modeling has succeeded to simulate the failure of the screwed shaft.